We've updated our
Privacy Policy effective December 15. Please read our updated Privacy Policy and tap

Study Guides > Intermediate Algebra

Read: Special Cases - Cubes

Learning Objectives

  • Factor the sum of cubes.
  • Factor the difference of cubes.
Some interesting patterns arise when you are working with cubed quantities within polynomials. Specifically, there are two more special cases to consider: a3+b3a^{3}+b^{3} and a3b3a^{3}-b^{3}. Let’s take a look at how to factor sums and differences of cubes.

Sum of Cubes

The term “cubed” is used to describe a number raised to the third power. In geometry, a cube is a six-sided shape with equal width, length, and height; since all these measures are equal, the volume of a cube with width xx can be represented by x3x^{3}. (Notice the exponent!) Cubed numbers get large very quickly. 13=11^{3}=1,    23=82^{3}=8,    33=273^{3}=27,    43=644^{3}=64,   and   53=1255^{3}=125. Before looking at factoring a sum of two cubes, let’s look at the possible factors. It turns out that a3+b3a^{3}+b^{3} can actually be factored as (a+b)(a2ab+b2)\left(a+b\right)\left(a^{2}–ab+b^{2}\right). Let’s check these factors by multiplying.

Example

Does (a+b)(a2ab+b2)=a3+b3(a+b)(a^{2}–ab+b^{2})=a^{3}+b^{3}?

Answer: Apply the distributive property.

(a)(a2ab+b2)+(b)(a2ab+b2)\left(a\right)\left(a^{2}–ab+b^{2}\right)+\left(b\right)\left(a^{2}–ab+b^{2}\right)

Multiply by a.

(a3a2b+ab2)+(b)(a2ab+b2)\left(a^{3}–a^{2}b+ab^{2}\right)+\left(b\right)\left(a^{2}-ab+b^{2}\right)

Multiply by b.

(a3a2b+ab2)+(a2bab2+b3)\left(a^{3}–a^{2}b+ab^{2}\right)+\left(a^{2}b–ab^{2}+b^{3}\right)

Rearrange terms in order to combine the like terms.

a3a2b+a2b+ab2ab2+b3a^{3}-a^{2}b+a^{2}b+ab^{2}-ab^{2}+b^{3}

Simplify.

Answer

a3+b3a^{3}+b^{3}

Did you see that? Four of the terms cancelled out, leaving us with the (seemingly) simple binomial a3+b3a^{3}+b^{3}. So, the factors are correct. You can use this pattern to factor binomials in the form a3+b3a^{3}+b^{3}, otherwise known as “the sum of cubes.”

The Sum of Cubes

A binomial in the form a3+b3a^{3}+b^{3} can be factored as (a+b)(a2ab+b2)\left(a+b\right)\left(a^{2}–ab+b^{2}\right).

Examples:

The factored form of x3+64x^{3}+64 is (x+4)(x24x+16)\left(x+4\right)\left(x^{2}–4x+16\right). The factored form of 8x3+y38x^{3}+y^{3} is (2x+y)(4x22xy+y2)\left(2x+y\right)\left(4x^{2}–2xy+y^{2}\right).
 

Example

Factor x3+8y3x^{3}+8y^{3}.

Answer: Identify that this binomial fits the sum of cubes pattern: a3+b3a^{3}+b^{3}. a=xa=x, and b=2yb=2y (since 2y2y2y=8y32y\cdot2y\cdot2y=8y^{3}).

x3+8y3x^{3}+8y^{3}

Factor the binomial as (a+b)(a2ab+b2)\left(a+b\right)\left(a^{2}–ab+b^{2}\right), substituting a=xa=x and b=2yb=2y into the expression.

(x+2y)(x2x(2y)+(2y)2)\left(x+2y\right)\left(x^{2}-x\left(2y\right)+\left(2y\right)^{2}\right)

Square (2y)2=4y2(2y)^{2}=4y^{2}.

(x+2y)(x2x(2y)+4y2)\left(x+2y\right)\left(x^{2}-x\left(2y\right)+4y^{2}\right)

Multiply x(2y)=2xy−x\left(2y\right)=−2xy (writing the coefficient first).

Answer

(x+2y)(x22xy+4y2)\left(x+2y\right)\left(x^{2}-2xy+4y^{2}\right)

And that’s it. The binomial x3+8y3x^{3}+8y^{3} can be factored as (x+2y)(x22xy+4y2)\left(x+2y\right)\left(x^{2}–2xy+4y^{2}\right)! Let’s try another one. You should always look for a common factor before you follow any of the patterns for factoring.

Example

Factor 16m3+54n316m^{3}+54n^{3}.

Answer: Factor out the common factor 22.

16m3+54n316m^{3}+54n^{3}

8m38m^{3} and 27n327n^{3} are cubes, so you can factor 8m3+27n38m^{3}+27n^{3} as the sum of two cubes: a=2ma=2m, and b=3nb=3n.

2(8m3+27n3)2\left(8m^{3}+27n^{3}\right)

Factor the binomial 8m3+27n38m^{3}+27n^{3} substituting a=2ma=2m and b=3nb=3n into the expression (a+b)(a2ab+b2)\left(a+b\right)\left(a^{2}-ab+b^{2}\right).

2(2m+3n)[(2m)2(2m)(3n)+(3n)2]2\left(2m+3n\right)\left[\left(2m\right)^{2}-\left(2m\right)\left(3n\right)+\left(3n\right)^{2}\right]

Square: (2m)2=4m2(2m)^{2}=4m^{2} and (3n)2=9n2(3n)^{2}=9n^{2}.

2(2m+3n)[4m2(2m)(3n)+9n2]2\left(2m+3n\right)\left[4m^{2}-\left(2m\right)\left(3n\right)+9n^{2}\right]

Multiply (2m)(3n)=6mn-\left(2m\right)\left(3n\right)=-6mn.

Answer

2(2m+3n)(4m26mn+9n2)2\left(2m+3n\right)\left(4m^{2}-6mn+9n^{2}\right)

Difference of Cubes

Having seen how binomials in the form a3+b3a^{3}+b^{3} can be factored, it should not come as a surprise that binomials in the form a3b3a^{3}-b^{3} can be factored in a similar way.

The Difference of Cubes

A binomial in the form a3b3a^{3}–b^{3} can be factored as (ab)(a2+ab+b2)\left(a-b\right)\left(a^{2}+ab+b^{2}\right).

Examples

The factored form of x364x^{3}–64 is (x4)(x2+4x+16)\left(x–4\right)\left(x^{2}+4x+16\right). The factored form of 27x38y327x^{3}–8y^{3} is (3x2y)(9x2+6xy+4y2)\left(3x–2y\left)\right(9x^{2}+6xy+4y^{2}\right).
Notice that the basic construction of the factorization is the same as it is for the sum of cubes; the difference is in the ++ and signs. Take a moment to compare the factored form of a3+b3a^{3}+b^{3} with the factored form of a3b3a^{3}-b^{3}. Factored form of a3+b3a^{3}+b^{3}(a+b)(a2ab+b2)\left(a+b\right)\left(a^{2}-ab+b^{2}\right) Factored form of a3b3a^{3}-b^{3}: (ab)(a2+ab+b2)\left(a-b\right)\left(a^{2}+ab+b^{2}\right) This can be tricky to remember because of the different signs—the factored form of a3+b3a^{3}+b^{3} contains a negative, and the factored form of a3b3a^{3}-b^{3} contains a positive! Some people remember the different forms like this: “Remember one sequence of variables: a3b3=(ab)(a2abb2)a^{3}b^{3}=\left(a\,b\right)\left(a^{2}ab\,b^{2}\right). There are 44 missing signs. Whatever the first sign is, it is also the second sign. The third sign is the opposite, and the fourth sign is always ++.” Try this for yourself. If the first sign is ++, as in a3+b3a^{3}+b^{3}, according to this strategy how do you fill in the rest: (ab)(a2abb2)\left(a\,b\right)\left(a^{2}ab\,b^{2}\right)? Does this method help you remember the factored form of a3+b3a^{3}+b^{3} and a3b3a^{3}–b^{3}? Let’s go ahead and look at a couple of examples. Remember to factor out all common factors first.

Example

Factor 8x31,0008x^{3}–1,000.

Answer: Factor out 88.

8(x3125)8(x^{3}–125)

Identify that the binomial fits the pattern a3b3:a=xa^{3}-b^{3}:a=x, and b=5b=5 (since 53=1255^{3}=125).

8(x3125)8\left(x^{3}–125\right)

Factor x3125x^{3}–125 as (ab)(a2+ab+b2)\left(a–b\right)\left(a^{2}+ab+b^{2}\right), substituting a=xa=x and b=5b=5 into the expression.

8(x5)[x2+(x)(5)+52]8\left(x-5\right)\left[x^{2}+\left(x\right)\left(5\right)+5^{2}\right]

Square the first and last terms, and rewrite (x)(5)\left(x\right)\left(5\right) as 5x5x.

8(x5)(x2+5x+25)8\left(x–5\right)\left(x^{2}+5x+25\right)

Answer

8(x5)(x2+5x+25)8\left(x–5\right)\left(x^{2}+5x+25\right)

Let’s see what happens if you don’t factor out the common factor first. In this example, it can still be factored as the difference of two cubes. However, the factored form still has common factors, which need to be factored out. As you can see, this last example still worked, but required a couple of extra steps. It is always a good idea to factor out all common factors first. In some cases, the only efficient way to factor the binomial is to factor out the common factors first. Here is one more example. Note that r9=(r3)3r^{9}=\left(r^{3}\right)^{3} and that 8s6=(2s2)38s^{6}=\left(2s^{2}\right)^{3}.

Example

Factor r98s6r^{9}-8s^{6}.

Answer: Identify this binomial as the difference of two cubes. As shown above, it is. Using the laws of exponents, rewrite r9r^{9} as (r3)3\left(r^{3}\right)^{3}.

r98s6r^{9}-8s^{6}

Rewrite r9r^{9} as (r3)3\left(r^{3}\right)^{3} and rewrite 8s68s^{6} as (2s2)3\left(2s^{2}\right)^{3}.

(r3)3(2s2)3\left(r^{3}\right)^{3}-\left(2s^{2}\right)^{3}

Now the binomial is written in terms of cubed quantities. Thinking of a3b3a^{3}-b^{3}, a=r3a=r^{3} and b=2s2b=2s^{2}. Factor the binomial as (ab)(a2+ab+b2)\left(a-b\right)\left(a^{2}+ab+b^{2}\right), substituting a=r3a=r^{3} and b=2s2b=2s^{2} into the expression.

(r32s2)[(r3)2+(r3)(2s2)+(2s2)2]\left(r^{3}-2s^{2}\right)\left[\left(r^{3}\right)^{2}+\left(r^{3}\right)\left(2s^{2}\right)+\left(2s^{2}\right)^{2}\right]

Multiply and square the terms.

(r32s2)(r6+2r3s2+4s4)\left(r^{3}-2s^{2}\right)\left(r^{6}+2r^{3}s^{2}+4s^{4}\right)

Answer

(r32s2)(r6+2r3s2+4s4)\left(r^{3}-2s^{2}\right)\left(r^{6}+2r^{3}s^{2}+4s^{4}\right)

In the following two video examples we show more binomials that can be factored as a sum or difference of cubes. https://youtu.be/tFSEpOB262M https://youtu.be/J_0ctMrl5_0   You encounter some interesting patterns when factoring. Two special cases—the sum of cubes and the difference of cubes—can help you factor some binomials that have a degree of three (or higher, in some cases). The special cases are:
  • A binomial in the form a3+b3a^{3}+b^{3} can be factored as (a+b)(a2ab+b2)\left(a+b\right)\left(a^{2}–ab+b^{2}\right)
  • A binomial in the form a3b3a^{3}-b^{3} can be factored as (ab)(a2+ab+b2)\left(a-b\right)\left(a^{2}+ab+b^{2}\right)
Always remember to factor out any common factors first.

Licenses & Attributions